The Problematics of Divorce Before Judges The Perspective of Islamic Law Compilation and Madzhab Syafi’i - Misnanto Misnanto (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2022)
Indonesia is country based on law, the law itself is regulation regarding human actions that can done or not done, Humans are social creatures whoo need others, in is marriage there are many problems cause divorce, then writer will analysisthe validity of divorce before the panel of judges according to Islamic Law Compilation and Syafi’I Madzhab, as weell as analysisthe determination the iddah period in the Islamic Law Compilation and the opinion of the Syafi’I Madzhab, by using method abalisis conten, with conclusion in Islamic Law Compilation all divorces in Indonesia must go through a court of law, whether marriage is legal or not, this provision inconsistent with the 2012 Indonesia ulema’ consensus and opinion the Syafi’I madzhab, because according the Shafi’I School there are only 7 things, 4 cases where the husband does not want or has not dropped his tread, the woman may apply to court, namely: The problem of not having a living, The problem the wife’s harm, The problem of having a disability, The problem the husband’s departure which is not clear, and 3 cases are the absolute authority of the court to resolve, namely: divorce due to illa’, divorce due to li’an, divorce due to zhihar.